Pengaruh Efikasi Diri dan Disposisi Matematis Terhadap Kemampuan Penalaran Matematis Peserta Didik Sekolah Dasar - Buulolo, Dorotea Solomasi; Zebua, Berta Swit Lady; Gulo, Delvin Saputri; Zebua, Delviat Indah Sari; Gulo, Desti Natalia; Hulu, Dwi Permatasari; Daeli, Artamefia Kristiani; Hulu, Arman Setiawan; Harefa, Edward (Indo-MathEdu Intellectuals Journal, 2024)
Mathematical reasoning aims to stimulate students to think, solve problems, and communicate information effectively. To achieve good mathematical reasoning, students need mathematical self-efficacy and disposition. So in this research, the approach used is quantitative to determine the relationship between students' self-efficacy, mathematical disposition, and mathematical reasoning abilities. The instruments used were a mathematics disposition questionnaire, self-efficacy questionnaire, mathematical reasoning ability, and learning outcomes tests. The independent variables are self-efficacy and mathematical disposition, while the dependent variable is mathematical reasoning ability. The research sample was selected using a simple random sampling technique so that all elements of the population had the same opportunity to be selected. The research respondents were students from class VI A and VI B at Tetehosi State Elementary School with a total of 62 people. And the research results show that self-efficacy and mathematical disposition have a significant influence on the mathematical reasoning abilities of students in elementary schools, and there is a significant influence between self-efficacy and mathematical disposition simultaneously on the mathematical reasoning abilities of students in elementary schools.